Prevalence and correlates of intimate partner violence in HIV-positive women engaged in transactional sex in Mombasa, Kenya. (November 2016) - Wilson, Kate S; Deya, Ruth; Masese, Linnet; Simoni, Jane M; Stoep, Ann Vander; Shafi, Juma; Jaoko, Walter; Hughes, James P; McClelland, R Scott
Summary: We evaluated the prevalence and correlates of intimate partner violence (IPV) in the past year by a regular male partner in HIV-positive female sex workers (FSWs) in Mombasa, Kenya. This cross-sectional study included HIV-positive women ≥18 years old who reported engagement in transactional sex at the time of enrolment in the parent cohort. We asked 13 questions adapted from the World Health Organization survey on violence against women about physical, sexual, or emotional violence in the past year by the current or most recent emotional partner (index partner). We used standardised instruments to assess socio-demographic and behavioural characteristics as possible correlates of IPV. Associations between IPV and these correlates were evaluated using univariate and multivariate logistic regression. Overall, 286/357 women (80.4%) had an index partner, and 52/357 (14.6%, 95% confidence interval 10.9%–18.2%) reported IPV by that partner in the past year. In multivariate analysis, women with severe alcohol problems (adjusted odds ratio 4.39, 1.16–16.61) and those experiencing controlling behaviours by the index partner (adjusted odds ratio 4.98, 2.31–10.74) were significantly more likely to report recent IPV. Recent IPV was common in HIV-positive FSWs. Interventions targeting risk factors for IPV, including alcohol problems and partner controlling behaviours, could help to reduce recurrent violence and negative health outcomes in this key population.